CRITICAL OF ADMINISTRATION COURT SYSTEM IN INDONESIA THAT IS NOT HARMONIZE YET WITH THE ELEMENT OF GOVERNMENT ADMINISTRATIVE DECISION (BESCHIKKING) BASED ON GOVERNMENT ADMINISTRATION ACT 2014 - Mubiina, Fathan Ali (Tadulako University, 2020)
State administrative law has reformed with a new paradigm. So that the alignment or harmonization of administrative court procedural law becomes important. Because at the Implementation level, harmonization is needed in level of understanding that is reformed in the legislation, especially Act of Republic Indonesia No. 30 of 2014. Therefore, this topic tries to remind the stakeholders in the field of law to understand the object extension of the Government Administrative Decision (beschikking) after Act No. 30 of 2014. So, things that are not in accordance with the new paradigm can be minimized. For this reason, in addition to the Law on Administration Procedural Law, stakeholders are required to improve themselves by looking at Act No. 30 of 2014. Because the expansion of the objects of the Government Administrative Decision as the a quo Law still has a paradigm difference with the Circular of the Supreme Court of the Republic of Indonesia (SEMA) No. 4 of 2016. The difference in paradigm ultimately led to the fact that were confusions and trouble in the implementation which was still ongoing until now. Then in this study using the normative juridical method.